Genetic Characterization of Tilapia Fish Species in the University Fish Farm, Umudike, Niger Delta, Eastern Nigeria - Okere, Akpevwe Efe; Flourizel, Igbani; Anyaele, Uka (Darul Yasin Al Sys, 2024)
This study was aimed at identification and characterization of tilapia species farmed in the University Fish Farm Umudike. Dichotonomous key was employed in the application of morphometric and meristic parameters in the characterization. Molecular characterization was carried out using Random Amplified Polymorphic DNA (RAPD) primer by Polymerase Chain Reaction (PCR) amplification. A total of three hundred (300) fish samples suspected to be tilapia were collected from the University Fish Farm for the study. Eleven (11) morphometric and five (5) meristic counts were studied. Deoxyribonucleic acid (DNA) was extracted from the caudal fin tissues of sixty- six (66) samples from the three hundred fish samples using the Chlorophenol Isoamyl alcohol Method. Morphometric and meristic parameters were analyzed using Principal Component Analysis (PCA) which separated all sampled tilapia species statistically into three different groups, showing specifically the parameters that accounted for this variation. The first 7 components explained 91.382 % total variability among the groups with body depth cosntributing 25.226 %, body weight 50.133 %, total length 5.969 %, standard length 3.9178 %, caudal peduncle 3.406 %, head length 3.1518 %, dorsal fin base length contributing 2.6903 % of the total variability. Cluster analysis (CA) was based on Jaccard’s similarity coefficient. The study revealed mostly polymorphic bands from all 10 RAPD primers with a size ranged from 300 – 1000 base pairs (bp). Wide range of intra specific variation was observed within the species. Results obtained revealed that 3 distinct groups of tilapia with resemblance of Oreochromis niloticus, Sarotherodon galilaeus and Hemichromis fasciatus were present in the University fish farm. From the study, body depth and length of caudal peduncle were some of the natural markers that successfully separated all sampled species. The information obtained from this study in future could be employed in improvement programme for enhanced economic benefit of tilapia faming in Michael Okpara University of Agriculture, Umudike (MOUAU) Fish Farm.